Human Newborn Monocytes Demonstrate Distinct BCG-Induced Primary and Trained Innate Cytokine Production and Metabolic Activation In Vitro - Angelidou, Asimenia; Diray-Arce, Joann; Conti, Maria-Giulia; Netea, Mihai G.; Blok, Bastiaan A.; Liu, Mark; Sanchez-Schmitz, Guzman; Ozonoff, Al; van Haren, Simon D.; Levy, Ofer (Frontiers in Immunology, 2021)
Background: Newborns exhibit distinct immune responses and are at high risk of infection. Neonatal immunization with BCG, the live attenuated vaccine against tuberculosis (TB), is associated with broad protection against a range of unrelated pathogens, possibly reflecting vaccine-induced training of innate immune cells (“innate memory”). However, little is known regarding the impact of age on BCG-induced innate responses. Objective: Establish an age-specific human monocyte in vitro training platform to characterize and compare BCG-induced primary and memory cytokine responses and immunometabolic shifts. Design/Methods: Human neonatal and adult CD33-selected monocytes were stimulated for 24h with RPMI (control) or BCG (Danish strain) in 10% autologous serum, washed and cultured for 5 additional days, prior to re-stimulation with the TLR4 agonist LPS for another 24h. Supernatants were collected at Day 1 (D1) to measure primary innate responses and at Day 7 (D7) to assess memory innate response by ELISA and multiplex cytokine and chemokine assays. Lactate, a signature metabolite increased during trained immunity, was measured by colorimetric assay. Results: Cytokine production by human monocytes differed significantly by age at D1 (primary, BCG 1:750 and 1:100 vol/vol, p<0.0001) and D7 (innate memory response, BCG 1:100 vol/vol, p<0.05). Compared to RPMI control, newborn monocytes demonstrated greater TNF (1:100, 1:10 vol/vol, p<0.01) and IL-12p40 (1:100 vol/vol, p<0.05) production than adult monocytes (1:100, p<0.05). At D7, while BCG-trained adult monocytes, as previously reported, demonstrated enhanced LPS-induced TNF production, BCG-trained newborn monocytes demonstrated tolerization, as evidenced by significantly diminished subsequent LPS-induced TNF (RPMI vs. BCG 1:10, p <0.01), IL-10 and CCL5 production (p<0.05). With the exception of IL-1RA production by newborn monocytes, BCG-induced monocyte production of D1 cytokines/chemokines was inversely correlated with D7 LPS-induced TNF in both age groups (p<0.0001). Compared to BCG-trained adult monocytes, newborn monocytes demonstrated markedly impaired BCG-induced production of lactate, a key metabolite for immune training. Conclusions: BCG-induced human monocyte primary- and memory-innate cytokine responses were age-dependent and accompanied by distinct immunometabolic shifts that impact both glycolysis and training. Our results suggest that immune ontogeny may shape innate responses to live attenuated vaccines, suggesting age-specific approaches to leverage innate training for broad protection against infection.